METHODOLOGICAL ISSUES IN DEVELOPING CRITICAL-OPERATIONAL COMMUNICATION IN THE TEACHING OF “MEDICAL RADIOLOGY” - Shukurova Sevara Ilhomovna (Bright Mind Publishing, 2025)
This article explores the issues of developing students' skills in critical-operational communication during the teaching of the “Medical Radiology” discipline through pedagogical dialogue. Modern medical education requires students not only to possess theoretical knowledge but also to make prompt decisions in clinical situations, engage in professional communication, and think critically. From this perspective, fostering critical-operational communication through meaningful and interactive forms of pedagogical dialogue is considered an important methodological task. The article analyzes the methodological foundations of this process, identifies existing challenges, and proposes innovative approaches to address them.
Keywords: Pedagogical dialogue, critical-operational communication, medical radiology, methodological problem, clinical thinking, case scenario, professional interaction, interactive learning, educational technologies.